Out of the limelight but in play: Trading and liquidity of media and off-media stocks - Fang, H.; Zhang, Huiping; Qian, J. (2014)
Using hand-collected TV programming data and intra-day trading from China, we compare the trading, liquidity, and returns of on-show and off-show stocks in the same sector. Our difference-in-difference analysis reveals that post-show, off-show stocks experience significant improvements in liquidity that is attributable to small trades. The pre-show return gap between the on-show and off-show stocks closes post-show, and there is no return reversal. We show that retail investors’ focus on off-show stocks could reflect a lack of media trust. Overall, our evidence suggests that media coverage facilitate price discovery and retail investors appear to respond rationally to media coverage.